Introduction to dossier. Inhabited urbanisms: The social life of the built environment in Latin America - Navas-Perrone, María Gabriela; Marcús, Juliana (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2023)
Introduction to dossier. Inhabited urbanisms: The social life of the built environment in Latin America